1981
DOI: 10.1071/ea9810623
|View full text |Cite
|
Sign up to set email alerts
|

Promalin improves the shape of Delicious apples in Victoria

Abstract: Results of two experiments and nine orchard trials over three seasons at eight fruit growing districts have shown that fruit shape of Richared, Lalla, Starking, Hi-Early and Common Delicious apples can be improved by applications of the commercial formulation of N-(phenylmethylkl H-purin-61 - 1 amine plus gibberellins A, + A, (Promalin). Promalin at 25 ppm significantiy increased both fruit length: diameter ratio and prominence of calyx lobes. These fruit were considered to have a more characteristic shape and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, it appears from the present study that fruit shape may also be influenced by the time of thinning in some cultivars, particularly 'Delicious', where thinning close to bloom reversed this trend towards flatter fruit. From a marketing perspective, fruit shape and typiness are important attributes in 'Delicious' and management practices that flatten the fruit impact on marketability [34,35].…”
Section: Fruit Shapementioning
confidence: 99%
“…However, it appears from the present study that fruit shape may also be influenced by the time of thinning in some cultivars, particularly 'Delicious', where thinning close to bloom reversed this trend towards flatter fruit. From a marketing perspective, fruit shape and typiness are important attributes in 'Delicious' and management practices that flatten the fruit impact on marketability [34,35].…”
Section: Fruit Shapementioning
confidence: 99%
“…In several mountainous apple-growing regions, air temperature is influenced by elevation. Veinbrants and Miller (1981) observed that fruit produced in northeastern Victoria, Australia, at relatively high elevations, tended to have the characteristic elongated Delicious shape because of low air temperature after blooming. However, many Delicious apples grown in the coastal areas of southern Victoria at low elevations and high air temperatures after blooming tended to be flat rather than elongated and do not assume the characteristic Delicious shape.…”
Section: Fruit Shape and Size Distributionmentioning
confidence: 99%
“…In addition Promalin improved the prominence of the calyx lobes equally at all concentrations. In Australia the plant growth regulator Cytolin (registered as Promalin in the USA) is commonly used to elongate and improve the shape of 'Delicious' [112,113,114,115].…”
Section: Shapementioning
confidence: 99%